INTRODUCTION OF THE GRAIN FUTURES MARKET IN THE BLACK SEA REGION - Kovačević, Vlado (Economics of Agriculture, 2018)
In this paper are analysed possibilities and mechanisms for developing grain futures in the Black Sea Region. The transition to the market economy in the agricultural sector of Romania, Bulgaria and Serbia reinforces the need for the development of market mechanisms that would allow agricultural producers, production planning, marketing, and hedging. In the early 21st century an attempt was made with the support of USAID to establish a wheat futures market for the countries of the Black Sea Region. The project was unsuccessful. The reasons lie primarily in the attempt to simultaneously involve a large number of countries that had: (1) different standards of wheat quality, (2) different and incompatible payment systems between countries, (3) customs barriers between countries, and so on. The proposal now is to precede with the establishment of futures markets in Serbia, Romania and Bulgaria, which have liberalized markets between themselves, and established a common legal EU framework related to the commodity derivatives market. After a successful introduction of the futures market for these three countries, other countries in the Black Sea Region can individually join the already formed system. A large volume of wheat futures trading is expected on the Black Sea futures market, littoral for two reasons. Firstly, a significant part of global trade in wheat is contracted for delivery to Black Sea ports. Secondly, the volatility of wheat prices has been notable in recent years, strengthening the need for the use of futures to insure wheat prices in the future. Romanian and Bulgarian membership in the World Trade Organization and the European Union, together with Serbian candidate status in both organisations guarantees that the market between those countries will remain liberalized. EU directives on investment protection schemes and a common derivatives market enforced for all EU countries will positively influence the grain futures market for the Black Sea Region.